Interpretacja projekcyjna. Prusowska lektura "Zdań i uwag" Adama Mickiewicza - Ławski, Jarosław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2014)
The article focuses on the interpretation of selected aphorisms of the Romantic poet Adam Mickiewicz (1798–1855) made by Bolesław Prus (1847–1912), a prose writer and representative of realism in Polish post-Romantic literature. Prus interpreted religious, sometimes almost mystical, aphorisms as commendation of hard work, activism, and as a manifesto of practical ethics. Inspired by the mystical thoughts of Angelus Silesius, Jacob Boehme and Saint-Martin, Mickiewicz’s aphorisms are perceived as exceptionally ambiguous. Prus, however, projected his own literary and philosophical mindset onto the micro-texts of the Romantic poet, and as a consequence oversimplified their meaning. What he did is here called a projecting interpretation.
A Projecting Interpretation. Prus’s Reading of Mickiewicz’s "Sentences and Remarks"
Keywords: aforyzm; mistyka; pozytywizm; realizm; reinterpretacja; aphorism; mystic; positivism; realism; re-interpretation